Mineral composition of and the relationships between them of human basal ganglia in very old age - Yoshiyuki Tohno (2018)
Trace elements and the relationships among them were investigated by direct chemical analysis in three basal ganglia regions in very old age individuals and age- and gender-related differences were assessed. After ordinary dissections at Nara Medical University were finished, the caudate nucleus, putamen, and globus pallidus belonging to the basal ganglia were removed from the identical cerebra of the subjects who consisted of 22 men and 23 women, ranging in age from 70 to 101 years (average age = 83.3 ± 7.5 years). After incineration with nitric acid and perchloric acid, the element contents were determined by inductively coupled plasma-atomic emission spectrometry. It was found that the Ca, P, and Mg contents increased significantly in the putamen with aging and the Mg content increased significantly in the globus pallidus with aging, but no elements increased significantly in the caudate nucleus with aging. Regarding the relationships among elements in the basal ganglia, extremely significant direct correlations were found among the Ca, P, and Mg contents in the putamen. These results suggested that slight calcification occurred in the putamen in very old age. With regard to seven elements of Ca, P, S, Mg, Zn, Fe, and Na, it was examined whether there were significant correlations among the caudate nucleus, putamen, and globus pallidus. It was found that there were extremely significant direct correlations among all of the three basal ganglia in the P content. Likewise, with regard to the Fe content, there were extremely or very significant direct correlations among all of the three basal ganglia. Regarding the gender difference in elements, it was found that the Ca content of the caudate nucleus was significantly higher in women than in men. © 2012 Springer Science+Business Media New York.